Estimation of the relative throughput of aircraft transponders of secondary airspace surveillance radar systems - Tkach, M.G. (Radiotekhnika, 2021)
Secondary radar systems for monitoring airspace play a significant role in the information support of airspace control systems and air traffic control. These systems provide radar surveillance of airborne objects equipped with aircraft transponders and provide two-way communication via data request and response channels between ground radar stations and airborne objects. The paper assesses the relative throughput of aircraft transponders of secondary radar systems for monitoring airspace under the influence of correlated and uncorrelated interference in the request channel. The assessment of the throughput of the aircraft transponder shows that the aircraft transponder does not reach the maximum load included in the existing identification system under the influence of deliberate correlated interference. This indicates a sub-optimal determination of the aircraft transponder load factor of the existing secondary radar system. Incorrect determination of the maximum load of the aircraft transponder leads to a decrease in the noise immunity of both the aircraft transponder and the entire secondary radar system. At the same time, it should be noted that the interested party has the possibility of unauthorized use of an aircraft transponder to obtain information or paralyze the latter when applying interference of the required intensity.